Genital fistula: Successes, challenges, and way forward in a facility specialization in fistula management in Bangladesh - Biswas, Nrinmoy; Mahmood, Iftikher; Doraiswamy, Sathyanarayan; Biswas, Animesh (Nepal Journal of Obstetrics and Gynaecology, 2019)
Aims: To explore the prevalence, types of genital fistulas as well as their success, challenges, and way forward on genital fistula in Bangladesh. Methods: Between October 2017 and September 2018, Hope Hospital identified a total number of 101 genital fistula cases though a community network system in Cox’s Bazar. For each of the patients, detailed case histories and clinical management reports documented, and the data were interpreted using descriptive analysis. Results: Out of 101 genital fistula cases admitted to the facility, 95.3% (n=96) of cases were obstetric; three cases iatrogenic, and one each traumatic and congenital. The median age of the women was 28 years (range: 18 -73) and the median duration of two years (range: 1 month-53 years). Most of the cases had urinary incontinence (86.1 %, n=85) and 12 and two cases were fecal and mixed type respectively. Vesicovaginal fistula (VVF) repair was performed in most of the cases (78.2%, n=79) while 21.8% (n=22) received recto vaginal fistula (RVF) repair. 90% (n=91) were discharged without complication. The median duration of hospital stay was 16 days (range: 4 -29). The success rate was 86.1% (n=85), and 16 cases advised for repeat surgery. Pre-and post-surgery counselling was provided without rehabilitation or reintegration support. Conclusions: Facility data in a particular geographic location represents high prevalence of obstetric fistula and lacks rehabilitation and social reintegration support. Further study is essential to draw a complete geographical map for genital fistula in Bangladesh. Keywords: genital fistula, management, rehabilitation, Bangladesh